2013
DOI: 10.1002/2013jc008994
|View full text |Cite
|
Sign up to set email alerts
|

A mesoscale eddy pair southwest of Taiwan and its influence on deep circulation

Abstract: [1] A pair of mesoscale eddies, namely, an anticyclonic eddy (AE) and a cyclonic eddy (CE), generated southwest of Taiwan was investigated using long-term moored observations augmented with satellite and reanalysis data. AE (CE) increased the upperocean current to 100 cm/s (50 cm/s) and generated temperature anomaly (T 0 ) up to 7.5 C (23.0 C). The vertical structure of AE presented a phase difference between T 0 and velocity, with the core of T 0 located south of the zero-velocity line. This phase difference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
104
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 151 publications
(112 citation statements)
references
References 63 publications
8
104
0
Order By: Relevance
“…Eddies have gained much attention since they are an important form of material and energy transfer in the ocean (Zhang et al, 2011(Zhang et al, , 2013(Zhang et al, , 2014Kersalé et al, 2013;Waite et al, 2007;Jacob et al, 2002;Wang et al, 2005). Although isolated eddies in open oceans are affected by different factors, many of them have similar kinematic characteristics in general.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eddies have gained much attention since they are an important form of material and energy transfer in the ocean (Zhang et al, 2011(Zhang et al, , 2013(Zhang et al, , 2014Kersalé et al, 2013;Waite et al, 2007;Jacob et al, 2002;Wang et al, 2005). Although isolated eddies in open oceans are affected by different factors, many of them have similar kinematic characteristics in general.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, mesoscale eddies occur frequently in the northern SCS (Hwang and Chen, 2000;Chang et al, 2012;Zhang et al, 2013;Nan et al, 2011;Wang et al, , 2005, and the number of cold eddies is similar to that of warm eddies. Therefore, it is of importance to find out the difference between the cold and warm eddies.…”
Section: Introductionmentioning
confidence: 99%
“…Some work has analyzed eddies' seasonal variability (Wu and Chiang, 2007;Zhuang et al, 2010) and investigated their origins (D. . Some work has mainly studied specific eddies to better understand eddies' generation, development, and disappearance mechanisms (G. Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In the SCS, many eddies are observed from in situ observations (Xu et al, 1982;Chu et al, 1998;Li et al, 1998;Hu et al, 2011;Zhang et al, 2013Zhang et al, , 2016 and satellite sea-level anomaly data (Li et al, 2002;Su et al, 2002;Yuan et al, 2007;Chow et al, 2008;Wang et al, 2008). counted the SCS mesoscale eddies using a merged satellite altimeter data set and found that eddies can be mainly grouped into four geographic zones in the SCS.…”
Section: Introductionmentioning
confidence: 99%
“…When the Kuroshio flows over the Luzon Strait, a meander sometimes forms and the mesoscale eddies may be shed from the unstable meander and propagate westward into the SCS (Li et al, 1998;Wang et al, 2000;Yang et al, 2000;Li et al, 2002;Su et al, 2002;Jia and Liu, 2004;Yuan et al, 2006;Zhang et al, 2013). The mesoscale eddy shedding event can occur all year round (Yuan, 2006).…”
Section: Introductionmentioning
confidence: 99%